โครงสร้างอิเล็กทรอนิกส์ประสิทธิผลแบบหนึ่งมิติของอินเดียมแกลเลียมอาร์เซไนด์ควอนตัมดอตโมเลกุล - นิธิเดช ธัชศฤงคารสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This thesis reports simulation results of an effective one dimension (1D) electronic structure of InGaAs quantum dot molecules (QDMs). Samples were grown by molecular beam epitaxy (MBE) using thin capping and regrowth technique. The first layer of InAs quantum dots (QDs) was grown with a thickness of 1.8 ML and capped by 15 ML and 25 ML of GaAs for samples A and B, respectively. Another layer of 1.2-ML InAs was regrown on this capping layer. This process resulted in the formation of ensemble of QDMs, each consists of one large QD at the center surrounded by smaller satellite QDs. Surface morphology and optical properties of InGaAs QDMs were studied by atomic force microscopy AFM and power- and temperature-dependent photoluminescence (PL) measurements. PL results were used to simulate the effective 1D electronic structure. Eigen energies of carriers obtained from the simulation can be used to explain the PL results at all temperatures. The accuracy of the model is better than 6.3 meV and 7.9 meV for samples A and B, respectively. The results of the effective 1D electronic structure of InGaAs QDMs show that the effective chemical compositions of QDs and intermediate layers are In0.77Ga0.23As and In0.6Ga0.4As, respectively. The model can also identify that the PL spectrum of sample A was the emission of the center QDs only, whereas in sample B both the center and satellite QDs contributed to the emission spectrum. The simulation results of the effective 1D electronic structure of InGaAs QDMs can be used to explain the optical properties of complex InGaAs QDMs with good accuracy in the 20-150 K range. The effective sizes of QDs from the simulation are smaller than those measured by AFM because of the surface state effect of QDs and size uncertainty due to the convolution effect of AFM.